2019
DOI: 10.1186/s12976-019-0109-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a high protein diet and liver disease in an in silico model of human ammonia metabolism

Abstract: Background After proteolysis, the majority of released amino acids from dietary protein are transported to the liver for gluconeogenesis or to peripheral tissues where they are used for protein synthesis and eventually catabolized, producing ammonia as a byproduct. High ammonia levels in the brain are a major contributor to the decreased neural function that occurs in several pathological conditions such as hepatic encephalopathy when liver urea cycle function is compromised. Therefore, it is impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 79 publications
(81 reference statements)
1
12
0
Order By: Relevance
“…In a recent study where authors created a mathematical model to determine changes in ammonia levels from variable dietary protein intake and varying liver enzyme activity, it was reported that CPS1 activity had by far the strongest effect on blood ammonia levels of any other enzyme of the model. They demonstrated that 50% of decreased CPS1 activity led to a more of doubling in blood ammonia levels, as well as the decrease of protein intake may decrease blood ammonia levels minimizing the risk of developing hepatic encephalopathy 16 . Further, it was recently demonstrated that using a metabolite panel reflecting defects in ammonia recycling, urea cycle and amino acid metabolism could detect patients at risk of hepatocellular carcinoma 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study where authors created a mathematical model to determine changes in ammonia levels from variable dietary protein intake and varying liver enzyme activity, it was reported that CPS1 activity had by far the strongest effect on blood ammonia levels of any other enzyme of the model. They demonstrated that 50% of decreased CPS1 activity led to a more of doubling in blood ammonia levels, as well as the decrease of protein intake may decrease blood ammonia levels minimizing the risk of developing hepatic encephalopathy 16 . Further, it was recently demonstrated that using a metabolite panel reflecting defects in ammonia recycling, urea cycle and amino acid metabolism could detect patients at risk of hepatocellular carcinoma 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In these circumstances, a nutritional supplement designed to address the specific metabolic issues associated with the condition may provide unique benefits. A variety of nutritional supplements targeting some aspect of the AUD responses are available or have been proposed [8][9][10][11][12][13][14][15][16][17][18][19][20]. However, none have corrected the disruptions in macronutrient metabolism that lead to hepatic steatosis [11].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of hepatic steatosis is not identical among those at risk for metabolic disease and those who present with AUD [17]. Hepatic steatosis can occur in part because of a limitation in mitochondrial function [18], and thus impaired fatty acid oxidative capacity [19]. Impaired fatty acid oxidation results in the channeling of fatty acids into triglyceride synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Hyperammonemia typically occurs when plasma ammonia levels are above 50 umol/L; the exposure of the central nervous system to such an environment can lead to encephalopathy at levels double that. 3 Changes in neuronal pH, neuronal membrane potentials, astrocytic swelling, altered neurotransmitter response, and changes in cerebral energy metabolism and reduced ATP are considered some of the mechanisms of ammonia neurotoxicity. 4,5 Hyperammonemic disorders can be due to liver dysfunction, side-effects from certain medications (valproic acid, topiramate, carbamazepine, thiazides, isoniazid, or chemotherapies), impaired circulation where portal vein flow to the liver is reduced (because of obstruction or surgical bypass), or inborn errors of metabolism.…”
Section: Introductionmentioning
confidence: 99%